ANALISIS PROSES BERPIKIR ANAK BERKEBUTUHAN KHUSUS (ABK) DALAM MENYELESAIKAN MASALAH MATEMATIKA DI SMP INKLUSI KOTA METRO (Studi Kasus pada Siswa Tunagrahita Ringan) - Nurain Suryadinata; Nurul Farida (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2016)
The aims of the research is to describe the thinking process at mild intellectual disability students to solve mathematics problem. The research was a descriptive qualitative. The subjects of the research was students of grade eight SMPN 5 Metro. Technique analyzing of the data were: (1) classifying the data, (2) presenting the data, and (3) concluding the data in each categories. The results of the research showed that thinking process for mild intellectual disability students : (1) mild intellectual disability students can establishnment understanding in thinking process; (2) mild intellectual disability students can’t establishnment opinion and students cant’t using the right strategy to solve mathematics problem; (3) mild intellectual disability can’t give conclusion.